Effect of transgenic resistance to wheat viruses on host plant vector virus relationship - Jimenez Martinez, E. (Idaho (EUA), 2003)
Sumario (En)
Ilus.; 42 ref.
Tesis (Dr)
Keywords: TRITICUM; HORDEUM; VIRUS DE LAS PLANTAS; VECTORES; PLANTAS TRANSGENICAS; GENOTIPOS; APHIDOIDEA; RHOPALOSIPHUM PADI